Adverse Radiographic Outcomes Following Operative Treatment of Medial Malleolar Fractures. (November 2018) - Hu, Jianping; Zhang, Chunlin; Zhu, Kunpeng; Zhang, Lei; Wu, Weiping; Cai, Tao; Ma, Xiaolong
Background: We initiated a retrospective study on ankle fractures to assess (1) the time needed for fracture union; (2) the incidence of adverse radiographic outcomes (AROs); (3) factors that might lead to AROs; and (4) whether AROs were associated with worse function and higher incidence of post-trauma osteoarthritis (PTOA). Methods: From 2007 to 2016, a total of 296 patients (169 women, 127 men; average age, 48.6 years; range, 20-84) were diagnosed with a medial malleolar fracture, whether isolated or in the setting of bi- or trimalleolar fractures, and underwent open reduction and internal fixation (ORIF) or percutaneous screw fixation (PSF). The interval to fracture union, radiographic outcomes, American Orthopaedic Foot & Ankle Society (AOFAS) score at 6 months postoperatively, and the incidence of PTOA were recorded. Risk factors were identified both in univariate and multivariate analysis. The average follow-up period was 52.0 months (range, 12-118). Results: The incidence of delayed union, nonunion, and malunion were 20.3%, 3.7%, and 4.4%, respectively. The interval to fracture union was 10.3 ± 6.4 weeks. In the multivariate analysis, the risk factors for AROs were tobacco use, vertical fractures, interposed soft tissue, and fair/poor reduction. Patients with AROs had significantly worse AOFAS score at 6 months postoperatively ( P < .001) and higher incidence of PTOA ( P < .001). Conclusion: AROs of medial malleolar fractures have an underestimated incidence rate and are associated with worse ankle function and higher incidence of PTOA. Risk factors including tobacco use, vertical fractures, interposed soft tissue, poor/fair reduction should be prudently taken into consideration when treating medial malleolar fractures. Level of Evidence: Level III, retrospective cohort study.